Urban Panning, Land Use Regulation, and Relocation - Onishi, Takashi; Ishiwatari, Mikio (World Bank, Washington, DC, 2013)
Reconstruction should include a range of measures to enhance safety: disaster prevention facilities, relocation of communities to higher ground, and evacuation facilities. A community should not, however, rely too heavily on any one of these as being sufficient, because the next tsunami could be even larger than the last. Communities also need to rebuild their industries and create jobs to keep their residents from moving away. The challenge is to find enough relocation sites that are on high enough ground and large enough, and to regulate land use in lowland areas. There are two tiers of local government in Japan, prefectures and local municipalities, which are responsible for disaster response and reconstruction. Municipal governments play the most important role because they are closest to the victims and the stricken areas. The prefectural governments are grappling with the broad reconstruction issues. All reconstruction plans aim at rebuilding towns and communities that are resilient to major disasters.